Novel Variant of the SLC4A1 Gene Associated with Hereditary Spherocytosis - Dżamila M. Bogusławska; Sebastian Kraszewski; Michał Skulski; Stanisław Potoczek; Kazimierz Kuliczkowski; Aleksander F. Sikorski (Biomedicines, 2023)
Hereditary spherocytosis (HS) refers to the group of the most frequently occurring non-immune hereditary hemolytic anemia in people of Caucasian central or northern European ancestry. HS is mainly associated with pathogenic variants of genes encoding defects in five membrane proteins, including anion exchanger 1 encoded by the SLC4A1 gene. In this study, in a family affected with HS, we identified a hitherto unreported AE1 defect, variant p.G720W. The result of it is most likely the HS phenotype. Molecular dynamics simulation study of the AE1 transmembrane domain may indicate reasonable changes in AE1 domain structure, i.e., significant displacement of the tryptophan residue towards the membrane surface connected with possible changes in AE1 function. The WES analysis verified by classical sequencing in conjunction with biochemical analysis and molecular simulation studies shed light on the molecular mechanism underlying this case of hereditary spherocytosis, for which the newly discovered AE1 variant p.G720W seems crucial.